Where Do Brazilian Immigrant Parents Obtain Information to Support the Healthful Energy Balance-related Behaviors of Their Preschool-age Children?: A Cross-sectional Study. Issue 1 (2nd January 2022) - Lindsay, Ana Cristina; Caires, Thaís; Le, Qun; Nogueira, Denise Lima; Tavares Machado, Márcia M.; Greaney, Mary L.
ABSTRACT: Background: Brazilians are a growing immigrant population in the United States and there is a lack of interventions to promote healthful energy balance-related behaviors (EBRBs) and prevent obesity among Brazilian preschool-age children. To develop needed interventions, information is required about parents' perceptions of the importance of EBRBs and where they obtain information about these behaviors. Purpose: To assess Brazilian immigrant parents' perception of the importance of EBRBs and information sources they use to support their preschool-age children's healthful EBRBs. Methods: Cross-sectional survey. Results: Fifty-two immigrant parents, most classified as having low acculturation, participated. In total, about 20–50% of parents perceived the six examined EBRBs as being extremely important. Parents reported that pediatricians, nurses, and WIC professionals were their primary sources for information about EBRBs. Discussion: Increased health education on the importance of EBRBs is needed. Health educators can facilitate linguistic and culturally sensitive communication, education, and provide guidance to parents on how to foster the development and maintenance of their preschool-age children's healthful EBRBs. Translation to Health Education Practice: Bicultural, bilingual health educators can help raise awareness, facilitate communication, provide education and guidance to Brazilian immigrant parents about the importance of children's healthful EBRBs in the prevention of obesity. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI)http://portal.shapeamerica.org/trn-Webinars/